Bromethalin poisoning in a raccoon (Procyon lotor): diagnostic considerations and relevance to nontarget wildlife. (January 2014) - Bautista, Adrienne C.; Woods, Leslie W.; Filigenzi, Mike S.; Puschner, Birgit
Submission of a raccoon ( Procyon lotor ) for necropsy following exhaustion at a California wildlife care center revealed minimal gross pathologic changes and only mild vacuolar changes in the white matter of the brain. Turquoise granular material was noted in the gastrointestinal tract and was submitted for toxicological testing along with portions of the brain, liver, kidney, and mesenteric and perirenal adipose tissues. Testing of the turquoise material for 7 anticoagulant rodenticides, strychnine, 4-aminopyridine, starlicide, and salts revealed none of these compounds; however, desmethylbromethalin was detected by high-performance liquid chromatography–tandem mass spectrometry. Other tissues were subsequently analyzed; the mesenteric and perirenal adipose tissues contained desmethylbromethalin. Desmethylbromethalin is the active metabolite of bromethalin, uncouples oxidative phosphorylation, and results in cerebral edema. Bromethalin is a rodenticide that is visually indistinguishable from many other rodenticides, making identification of poisonings by appearance alone nearly impossible. Based on the pathological and toxicological findings, a diagnosis of bromethalin toxicosis was established. In cases of wildlife species with unknown deaths or inconsistent clinical signs with normal or minimal histological findings, bromethalin toxicosis should be considered as a differential. Adipose tissue is the tissue of choice and can be easily harvested from a live or deceased animal to help confirm or rule out bromethalin exposure or intoxication.